Uczestnictwo studentów Uniwersytetu Zielonogórskiego w kulturze. Komunikat z badań = University of Zielona Góra students` participation in cultural activities - Narkiewicz-Niedbalec, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper presents the results of research on the University of Zielona Gora students` participation in cultural activities. Students have a fairly lively social life, going to pubs and clubs or using social networking websites (e.g. Skype, Gadu-Gadu). They are involved primarily in popular culture - they listen to pop music, watch TV and go to the cinema. They much less frequently go to the theatre and philharmonic. However, students read a lot more than adult Poles and their favourite genre is fantasy.
Keywords: Uniwersytet Zielonogórski; studenci; kultura